Açai (Euterpe oleracea, Mart.), an Amazonian fruit has antitumor effects on prostate cancer cells - Jobim, Micheli Lamberti; Barbisan, Fernanda; Fortuna, Milena; Teixeira, Cibele Ferreira; Boligon, Aline Augusti; Ribeiro, Euler Esteves; Cruz, Ivana Beatrice Mânica da (Archives in Biosciences & Health, 2019)
Açai (Euterpe oleracea, Mart.) is fruit broadly consumed in the world. From its chemical matrix is possible that açai could has some cytotoxic effect against prostate cancer (PCa). To test this hypothesis using an in vitro PCa model DU145 cell. Additionally, potential synergism between açai and docetaxel (DO), a chemotherapic drug used to treat advanced PCa was also evaluated. Cells were exposed an açai hydro alcoholic extract at different concentrations (1 to 1000 μg/mL) and its effect on viability, apoptosis and cellular proliferation was determined by MTT assay, growth cell, clonogenic assays and cell cycle analysis by flow cytometry. Differential modulation of Bcl-2 and BAX genes was also determined by Pcr quantitative in real time (qRT-PCR) analysis. Açai at lower concentrations (1-10 μg/mL) presented significant cytotoxic and antiproliferative action against PCa cells decreasing frequency of S phase cycle. Probably, this effect was associated with its strong down-regulation of Bcl-2 gene. However, açai did not contribute to improve Docetaxel effect´s on PCa cells. Açai’s PCa antitumor effects could be related to elevate concentrations of orientin plus vitexin, p-coumaric acid, apigenin and catechins present its chemical matrix, which are molecules with antitumor effect previously described in the literature.